The electronic structure of Ag1−xSn1+xSe2 (x = 0.0, 0.1, 0.2, 0.25 and 1.0). Issue 39 (2nd October 2017) - Wakita, Takanori; Paris, Eugenio; Kobayashi, Kaya; Terashima, Kensei; Hacisalihoǧlu, Muammer Yasin; Ueno, Teppei; Bondino, Federica; Magnano, Elena; Píš, Igor; Olivi, Luca; Akimitsu, Jun; Muraoka, Yuji; et al.
Abstract : Distinct valence electronic structures of SnSe and Ag1− x Sn1+ x Se2 are revealed by a combined analysis of X-ray absorption and X-ray photoemission spectroscopies. Abstract : We have studied the valence electronic structure of Ag1− x Sn1+ x Se2 ( x = 0.0, 0.1, 0.2, 0.25) and SnSe ( x = 1.0) by a combined analysis of X-ray absorption spectroscopy (XAS) and X-ray photoemission spectroscopy (XPS) measurements. Both XAS and XPS reveal an increase in electron carriers in the system with x ( i.e. excess Sn concentration) for 0 ≤ x ≤ 0.25. The core-level spectra (Sn 3d, Ag 3d and Se 3d) show that the charge state of Ag is almost 1+, while that of of Sn splits into Sn 2+ and Sn 4+ (providing clear evidence of valence skipping for the first time) with a concomitant splitting of Se into Se 2− and Se 2− δ states. The x dependence of the split components in Sn and Se together with the Se-K edge XAS reveals that the Se valence state may have an essential role in the transport properties of this system.